Genome-Wide Association Study Reveals Novel Genetic Loci for Quantitative Resistance to Septoria Tritici Blotch in Wheat (Triticum aestivum L.) - Mekonnen, Tilahun; Sneller, Clay H.; Haileselassie, Teklehaimanot; Ziyomo, Cathrine; Abeyo, Bekele G.; Goodwin, Stephen B.; Lule, Dagnachew; Tesfaye, Kassahun (Frontiers in Plant Science, 2021)
Septoria tritici blotch (STB) caused by the fungus Zymoseptoria titici poses serious and persistent challenges to wheat cultivation in Ethiopia and worldwide. Deploying resistant cultivars is a major component of controlling STB. Our objective was targeted to elucidate the genomic architecture of STB resistance in an association panel of 178 bread wheat genotypes. The association panel was phenotyped for STB resistance, phenology, yield and yield-related traits at three locations for two years. The panel was genotyped for SNP markers using Genotyping-by-sequencing (GBS), and a total of 7,776 polymorphic SNPs were used in subsequent analysis. Marker-trait associations were computed using GAPIT. Broad-sense heritability for STB resistance ranged from 0.58 - 0.97 and 0.72 - 0.81 at individual and across-environment levels, respectively, indicating the presence of STB resistance alleles in the association panel. Population structure and principal component analysis detected two sub-groups with a greater degree of admixture. LD analysis in 338,125 marker pairs detected the existence of significant (p  0.01) linkage between 27.6% of the marker pairs. In all chromosomes, LD between SNPs declined within 2.26 - 105.62 Mbp, with an overall mean of 31.44 Mbp. The association analysis identified 53 loci significantly (FDR <0.05) associated with STB resistance, pointing to 33 putative QTLs. Most of these shared similar chromosome with already published Septoria resistance genes which were distributed across chromosomes 1B, 1D, 2A, 2B, 2D, 3A, 3B, 3D, 4A, 5A, 5B, 6A, 7A, 7B and 7D. However, five of the putative QTLs identified on chromosomes 1A, 5D and 6B, appeared to be novel. Dissecting the detected loci on IWGSC RefSeq Annotation v2.1 revealed the existence of disease resistance-associated genes in the identified QTL regions which are involved in plant defense responses. The putative QTLs explained 2.7 - 13.2% of the total phenotypic variation. Seven of the QTLs (R2 = 2.7-10.8%) for STB resistance also co-localized with MTAs for agronomic traits. Overall, the present analysis reports on putative QTLs for adult-plant resistance to STB and some important agronomic traits. Previously, reported and novel QTL were identified indicating the potential to improve STB resistance by pyramiding the QTLs using marker-assisted selection.